Visitor Experience as a Source of Architectural Interpretation on the Building Elements of the Ratu Boko Palace Site - Dita Melindasari, Tiara; Surya, Vincentia Reni Vita; Herliana, Emmelia Tricia (Nature: National Academic Journal of Architecture, 2025)
The Ratu Boko Palace site is an 8th-century archaeological site with high historical, cultural, and spiritual value. However, the presentation of information at this site is still limited, so it has not yet built a deep interpretive experience for visitors. This study aims to (1) identify visitor profiles and perceptions, (2) map the routes and visual quality of viewpoints, and (3) evaluate the presentation of information in order to formulate a strategy for interpreting the site's architectural elements. The research method used mixed methods through questionnaires to 22 respondents, qualitative interviews, and spatial analysis using GPS Maps Camera. The analytical framework refers to Tilden's principles of cultural heritage interpretation and the UNESCO-ICOMOS conservation concept to ensure alignment with preservation standards. The results show that the majority of visitors are aged 31-40 years old with an interest in history and culture. The visit route is centered on the main gate, while other elements such as the pendapa, keputren, and cave are rarely visited. The information media was only rated “adequate” in terms of accuracy, readability, and relevance, indicating that the interpretation is still descriptive and lacks digital elements. These findings confirm the gap between visitor needs and the existing interpretation system. The study recommends the development of digital media such as QR codes, audio guides, and virtual tours to enrich the interpretive experience and support the preservation of cultural heritage sites.